Paul Nelson, Henry Wilkes, and L. D. Anderson painting the steeple on Calvary Moravian Church, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 3-10-64 p.8.
Paul Nelson, Henry Wilkes, and L. D. Anderson painting the steeple on Calvary Moravian Church, 1964. The church is located at 600 Holly Avenue.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth